2014
DOI: 10.1080/19345747.2014.921259
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Analysis in Educational Evaluation: A Case Study from the New York City Voucher Program

Abstract: We use quantile treatment effects estimation to examine the consequences of the random-assignment New York City School Choice Scholarship Program (NYCSCSP) across the distribution of student achievement. Our analyses suggest that the program had negligible and statistically insignificant effects across the skill distribution. In addition to contributing to the literature on school choice, the paper illustrates several ways in which distributional effects estimation can enrich educational research: First, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Specifically, the result that additional instructional time are more beneficial to higher achievers has implications for the growth and persistence of achievement gaps (Bitler et al, 2015) and is consistent with the theory that "skills beget skills." Identifying the mechanisms underlying these results is outside the scope of the current study, but would be useful for future research to consider.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, the result that additional instructional time are more beneficial to higher achievers has implications for the growth and persistence of achievement gaps (Bitler et al, 2015) and is consistent with the theory that "skills beget skills." Identifying the mechanisms underlying these results is outside the scope of the current study, but would be useful for future research to consider.…”
Section: Discussionsupporting
confidence: 58%
“…While average effects are interesting and add to our understanding of the relationship between instructional time and student outcomes, they overlook potential variation across the achievement distribution in the relationship between instructional time and student achievement (Bitler, Domina, Penner, and Hoynes, 2015;Eide and Showalter, 1998). We begin to fill this gap in the literature by extending the identification strategy pioneered by Fitzpatrick et al (2011) to the quantile regression context.…”
Section: Exploit Quasi-random Variation In Test Dates In the Earlymentioning
confidence: 99%
“…The inverse-propensity score weighted quantile treatment effects, which are described in more detail above, produce unconditional estimates of the impact of TFA on the distribution of student achievement, adjusting for the block randomization design, baseline control variables, previously identified missing values, and the previously unidentified missing values described above (c.f. Bitler, Domina, Penner, & Hoynes, 2015; Bitler, Gelbach, & Hoynes, 2006; Firpo et al, 2009). The process of conditioning, or including covariates, “shifts” an observation’s placement in the conditional distribution (Powell, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…To date, researchers have conducted 16 evaluations of the impact of school choice on participants' academic achievement using random assignment methods in the United States. Of those 16 evaluations, 10 found statistically significant positive gains on student achievement for some or all students (Rouse, 1998;Greene, Peterson, & Du, 1999;Greene, 2000;Howell, Wolf, Campbell, & Peterson, 2002 (contains three studies); Barnard et al, 2003;Cowen, 2008;Jin, Barnard, & Rubin, 2010;Bitler et al, 2015), four found no impact (Krueger & Zhu, 2004;Bettinger & Slonim, 2006;Wolf et al, 2013;, and two found negative impacts on academic achievement as a result of voucher use (Abdulkadiroglu, Pathak, & Walters, 2015;Dynarski et al, 2017).…”
Section: Student Achievementmentioning
confidence: 99%